PERANCANGAN TATA LETAK FASILITAS MENGGUNAKAN METODE BLOCPLAN “STUDI KASUS TOKO OLEH-OLEH SURABAYA HONEST” - Latifa Nur Sholekhah; Alif Rizki Rahardian; Diah Anisa Permata Sari; Dimas Qhoirul Huda; Rizal Qoiron; Evi Yuliawati (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
Surabaya Typical Souvenirs "HONEST" is a shop that sells Surabaya specialties which are available in almost all areas of Surabaya, both East Surabaya, North Surabaya, West Surabaya, South Surabaya, and some are in the Sidoarjo area. One of the drawbacks is the layout facilities, namely the position of placing the storefront which is too boring so that it makes customers who come uncomfortable and less interested in the placement of the store layout. To increase customer interest regarding the layout, it can be improved by redesigning the facility layout. The proposal for improving the facilities was taken because there is still a lot of empty space in the typical Surabaya souvenir shop "HONEST" so that it can be maximized to support customer facilities. The area approach in the typical Surabaya souvenir shop "HONEST" uses the Activity Relationship Chart (ARD) and Activity Relationship Diagram (ARD) methods. The two methods resulted in 2 areas that had to be brought closer together and became proposed improvement areas, namely the parking area and the waiting area. After the proposed area is known, enter the bloc plan stage, at this stage 3 proposed plans are produced from the proposed area chosen by the respondents